New GMT material suitable for various polymers and high glass fibre content. (April 2015) - Jung, G.; Mitschang, P.; Park, C.
Abstract : As a kind of long fibre reinforced thermoplastic, a new glass mat thermoplastic (GMT)-like material is introduced. It is designed to be suitable for various polymers and high glass fibre (GF) content, which might be a promising attempt to overcome the limit of conventional GMT material (PP matrix and maximum 40 wt-% GF). The concept is based on a multi-layered hybrid structure consisting of several thin GF sub-layers and polymer films having an inherently high viscosity. They are then needle-matted all together. The capability of higher GF content was derived from the porosity changes under pressure and the cross-sectional view after impregnation. It was finally confirmed by measurement of flexural properties up to 70 wt-% of GF content in PP grade. Moreover, PA6 grade was investigated to show the other capability of multi-layered hybrid mat for various polymers.